2019
DOI: 10.1080/21645515.2018.1558689
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of an adjuvanted recombinant zoster vaccine in older adults in the United States who have been previously vaccinated with zoster vaccine live

Abstract: Zoster Vaccine Live (ZVL) is marketed in the US since 2008, and a non-live adjuvanted Recombinant Zoster Vaccine (RZV) was approved in 2017. Literature suggests that waning of ZVL efficacy may necessitate additional vaccination. The Advisory Committee on Immunization Practices recommended vaccination with RZV in immunocompetent adults aged 50+ years old, including those previously vaccinated with ZVL. The objective of this study was to determine the cost-effectiveness of vaccinating US adults aged 60+ years ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 22 publications
1
15
0
Order By: Relevance
“…1 displays the PRISMA flow diagram describing the article selection process. A total of eleven published studies assessing the cost-effectiveness of herpes zoster vaccines met the inclusion and exclusion criteria ( Wilson et al, 2020 , Carpenter et al, 2019 , Curran et al, 2019 , Prosser et al, 2019 , Curran et al, 2018 , Dooling et al, 2018 , Le and Rothberg, 2018 , Le and Rothberg, 2018 , Le and Rothberg, 2017 , Le and Rothberg, Feb 2017 , Le and Rothberg, 2015 ). Four studies exclusively used ZVL, which has been removed from the U.S. marketplace.…”
Section: Resultsmentioning
confidence: 99%
“…1 displays the PRISMA flow diagram describing the article selection process. A total of eleven published studies assessing the cost-effectiveness of herpes zoster vaccines met the inclusion and exclusion criteria ( Wilson et al, 2020 , Carpenter et al, 2019 , Curran et al, 2019 , Prosser et al, 2019 , Curran et al, 2018 , Dooling et al, 2018 , Le and Rothberg, 2018 , Le and Rothberg, 2018 , Le and Rothberg, 2017 , Le and Rothberg, Feb 2017 , Le and Rothberg, 2015 ). Four studies exclusively used ZVL, which has been removed from the U.S. marketplace.…”
Section: Resultsmentioning
confidence: 99%
“…15 The annual rates of initial and recurrent cases of HZ and rates of associated PHN and nonpain complications (i.e., ocular, neurological, cutaneous, and other nonpain complications) were considered in the model; the default values and assumptions for these epidemiological inputs have been described previously. 16,17 Vaccine efficacy, waning of efficacy, and adverse event inputs used in this model also have been described previously. 16,18 Efficacy against HZ and PHN was included for those vaccinated with RZV and ZVL, with the baseline efficacy for each vaccine varying by age and with efficacy waning based on the years since vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Each replication tracked a cohort of individuals year by year over a period of 1 to 15 years through a number of possible health states, consistent with previous costeffectiveness analyses for RZV. 16,17 The…”
Section: Kpsc Case Studymentioning
confidence: 99%
“…The US adaptation was also updated to examine the potential cost effectiveness of revaccinating adults who had previously been immunized with ZVL. The results demonstrated that vaccination with RZV is cost effective compared to no vaccination at $100,000 WTP in those previously immunized with ZVL [41]. Finally, two independent models including RZV and ZVL have recently been developed for the US context.…”
Section: Discussionmentioning
confidence: 99%